2015
DOI: 10.1007/s12018-015-9185-x
|View full text |Cite
|
Sign up to set email alerts
|

Bone Turnover Markers: A Clinical Review

Abstract: The clinical applicability of bone turnover markers (BTMs) has been a reality in recent years with the accumulated experience on their performance in patients at risk of fracture and on the early prediction of the therapeutic response to anti-resorptive and anabolic drugs in osteoporosis. In addition, BTMs are also useful for analyzing the activity and the therapeutic response in other bone diseases, such as Paget's disease of bone. The main sources of variability have been substantially reduced with the use o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 107 publications
(168 reference statements)
0
3
0
Order By: Relevance
“…2c, d ). The upregulation of serum bone-resorption biomarkers 30 , CTX-I and TRAP5b, in Nron OCs−/− mice indicated that osteoclast-specific Nron knockout enhances bone-resorption activities of Nron OCs−/− mice (Fig. 2a ).…”
Section: Resultsmentioning
confidence: 97%
“…2c, d ). The upregulation of serum bone-resorption biomarkers 30 , CTX-I and TRAP5b, in Nron OCs−/− mice indicated that osteoclast-specific Nron knockout enhances bone-resorption activities of Nron OCs−/− mice (Fig. 2a ).…”
Section: Resultsmentioning
confidence: 97%
“…Among the indices of bone formation, the bone isoenzyme of alkaline phosphatase, osteocalcin and PINP are the most widely used. Several collagen degradation products, such as crosslaps (telopeptide of type I collagen), and TRAP5b, an enzyme highly expressed by osteoclasts, are some of the best known markers of bone resorption [15 ] .…”
Section: Bone Remodelingmentioning
confidence: 99%
“…New bone turnover markers were developed and measurements became more accurate. However, there is biological variability in BMTs due to age, sex, physical activity, recent fractures, or intercurrent disease ( 139 ). Due to these factors, interpretation of BMTs in rare metabolic bone disorders can be difficult.…”
Section: Discussionmentioning
confidence: 99%